Experimental investigation into vertical extension behavior of coal-measure tight sandstone reservoirs - Shao Mingren; Li Bin; Wang Peng; Wang Kunjian; Yang Qi; Sun Zening; An Qi (Scientific Reports)
Abstract The vertical fracture propagation morphology in sand-coal interbedded reservoirs is predominantly governed by interlayer mechanical relationships, intra-layer petrophysical properties, and fracturing operation parameters. This study conducted physical simulation experiments on sand-coal interbedded combinations using a large-scale true triaxial hydraulic fracturing system, investigating the effects of in-situ stress, injection rate, interfacial cementation strength, rock stacking patterns, and fracturing fluid viscosity on vertical fracture morphology. The experimental findings reveal: The vertical stress difference coefficient can be defined as the interlayer penetration criterion. Specifically, when the minimum vertical stress difference coefficient requirement is satisfied while other conditions act as secondary factors, fracture penetration across layers becomes feasible. However, due to coal seams’ inherent characteristics of well-developed cleat systems and strong water absorbency, achieving interlayer penetration proves more challenging in coal layers compared to sandstone formations. A higher injection rate facilitates fracture communication with adjacent layers and interfacial intersections, while controlled injection rates prove effective in restraining fracture height extension. Fractures exhibit greater penetration capability through high-strength cemented interfaces, whereas they preferentially propagate along low-strength interfacial zones; Elevated fracturing fluid viscosity promotes energy retention by minimizing fluid loss, thereby enhancing interlayer penetration—this viscosity-dependent mechanism provides an effective approach for fracture height containment.